Pengaruh Interval Pemberian Air melalui Irigasi Tetes (Drip Irrigation) dan Pupuk Mineral Plus terhadap Produksi Anggur pada Lahan Kering di Kecamatan Gerokgak Kabupaten Buleleng - MERIT, I NYOMAN; NARKA, I WAYAN (AGRITROP; Vol. 26, No. 1 Maret 2007, 2012)
A field experiment of drip irrigation was set up in the field on dry land farming at Patas Gerokgak, Buleleng. The aim of the experiment was to demonstrate to the local farmer about the beneficial goal of drip technology in order to gain a high efficiency of water application. Three intervals of water application, i.e. : 2 days, 4 days and 6 days (I1, I2, I3) in drip technique, and application of Mineral Plus fertilizers (M1) and without Mineral Plus fertilizers (M0) was observed in a nested block design. Bali grape varieties were used as an indicator. Parameters which were observed in second year experiment included the water distribution as indicated by soil water content at 0 – 15 cm depth, and soil water matrix potential (0 – 30 cm depth) which indicated by Loctonic tensiometer. Plant growth was observed by measuring fresh and dry weight biomass and diameter of grape stalk, regularly. The result of the experiment showed that, soil water content of 0 – 15 cm depth was not significantly affected by the treatment. Plant growth as indicated by fresh weight of biomass, dry weight of biomass and diameter of grape stalk were not significantly affected by the treatment There were no significant differences between treatments on fresh and dry weight biomass, dry biomass and diameter of grape stalk so that the yield of grape as indicated by number bunch of grape per plant, fresh weight of grape per bunch, fresh weight of grape per plant, dry weight of grape per bunch, number of grape per bunch were not significantly affected by the treatment. Yield quality as indicated by volume of grape per pellet, sugar content of grape and colour of grape were no significant differences between treatments.
Keywords: grape, fertilizers, intervals of water application